Modeling oligopolistic price adjustment in micro level panel data - Jürgen Bracht; Saul Lach; Eyal Winter (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2002)
Consumer prices in many markets are persistently dispersed both across retail outlets and over time. While the cross sectional distribution of prices is stable, individual stores change their position in the distribution over time. It is a challenge to model oligopolistic price adjustment to capture these features of consumer markets. In belief based models of price adjustment stores react to expected profits. The expectations are based on the observed vector of market prices in the previous periods. In a reinforcement model of price adjustment, if a strategy has proven fruitful in the past, it is apt to be the strategy relied upon at the present. We collect price data on a homogeneous consumer product in Israel. We estimate the structural parameter of the models. We find that the reinforcement model describes the data better than the belief based models. – – Preise für viele Konsumgüter sind weit verteilt. Dies gilt sowohl für die Verteilung über die Zeit als auch für die Verteilung zwischen den Verkaufsstellen. Während die Querschnittsverteilung der Preise stabil ist, wechseln die einzelnen Verkaufsstellen ihre Position in der Verteilung über die Zeit. Es stellt eine Herausforderung dar, diese Merkmale der Märkte für Konsumgüter zu modellieren. Im Vermutungslernen bilden die Verkaufstätten Erwartungen über das zukünftige Preissetzungsverhalten der Konkurrenz. Die Erwartungen basieren auf dem vorherigen Entscheidungsverhalten der Konkurrenz. Im Bekräftigungslernen werden erfolgreiche Strategien gerne wiederholt. Preisdaten eines homogenen Gutes in Israel werden erhoben. Die strukturellen Parameter der Modelle werden geschätzt. Bekräftigungslernen beschreibt das tatsächliche Entscheidungsverhalten besser als Vermutungslernen.
Keywords: C72; C91; D83; 330; Experiments; Information; Learning